Assessment of endothelial function by flow-mediated dilation in diabetic patients: Effects of physical exercise - Aline P Jarrete; Angelina Zanesco; Maria Andréia Delbin (Universidade Estadual Paulista (UNESP), 2016)
Abstract The endothelium is now recognized as an endocrine organ that acts to maintain vascular homeostasis regulating the vascular tone and structure. The endothelial cells synthetize a variety of mediators among them, the main agent is the nitric oxide (NO), a potent vasodilator. NO exerts its protective role preventing leukocyte adhesion and migration, expression of adhesion molecules, platelet aggregation, cell proliferation, and promoting the relaxation of smooth muscle cells. On the other hand, endothelial dysfunction present in many chronic diseases such as atherosclerosis, coronary artery disease, peripheral artery disease, hypertension and diabetes mellitus, is characterized by reduced NO bioavailability. Thus, a few decades ago, measurement of endothelial function has emerged as valuable tool that provides insights in the pathophysiological mechanisms, opportunity to identify early disease and cardiovascular risk, preventing future events or avoiding the progression of the disease. Diabetic patients, particularly, have been a target to apply this technique, mainly because this condition has been related with an impairment of endothelium-dependent dilation and it is believed that the endothelium dysfunction is the basis of diabetes complications such as coronary artery disease and accelerated atherosclerosis. In addition, cardiovascular complications represent the leading cause of morbidity and death in diabetes mellitus. Besides pharmacological therapy, lifestyle modifications have been recommended by specific organizations as a strategy to improve the endothelial function or even prevent the development of diabetes. The aim of this mini eview is to give an update about the importance of endothelium, most common non-invasive technique to evaluate its function, and to summarize some mechanisms involved in endothelial dysfunction and the beneficial effects of exercise in diabetes mellitus.